Lingkungan Keluarga dan Pengaruhnya terhadap Motivasi Belajar Siswa di Madrasah Ibtidaiyah - Herlina Herlina; Ajun Rois; Dinatul Munawaroh (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2021)
This study aims to examine whether there is an influence of the family environment on students' learning motivation at MI Al-Khoeriyah Cigudeg, Bogor Regency. The research sample was fifth grade students at MI Al-Khoeriyah. Research data were collected using questionnaires and documentation techniques. The research instrument used a questionnaire for the family environment and for learning motivation. The data analysis technique used a simple linear regression test and the interpretation of the data was carried out in a deductive narrative. The results showed that there was a significant correlation between variable X (family environment) and variable Y (student learning motivation) of 0.617. The significance level obtained is a significant value of 0.002 which is smaller than = 0.050 (one-tailed test or one-tailed test), so Ho: ρ = 0 is rejected. This means that there is a significant relationship between the family environment and the learning motivation of students at MI Al-Khoeriyah Cigudeg, Bogor Regency. The form of a simple linear regression equation is obtained = 47.122 + 0.205X. Based on the value of R square, the regression equation can be explained that 38.1% of the variance of student motivation at MI Al-Khoeriyah Cigudeg Bogor Regency can be explained by changes in the family environment.